Novel Azido-Iodo Photoaffinity Ligands for the Human Serotonin Transporter Based on the Selective Serotonin Reuptake Inhibitor (S)-Citalopram - Kumar, Vivek (J Med Chem, 2015)
[Image: see text] Three photoaffinity ligands (PALs) for the human serotonin transporter (hSERT) were synthesized based on the selective serotonin reuptake inhibitor (SSRI), (S)-citalopram (1). The classic 4-azido-3-iodo-phenyl group was appended to either the C-1 or C-5 position of the parent molecule, with variable-length linkers, to generate ligands 15, 22, and 26. These ligands retained high to moderate affinity binding (K(i) = 24–227 nM) for hSERT, as assessed by [(3)H]5-HT transport inhibition. When tested against Ser438Thr hSERT, all three PALs showed dramatic rightward shifts in inhibitory potency, with K(i) values ranging from 3.8 to 9.9 μM, consistent with the role of Ser438 as a key residue for high-affinity binding of many SSRIs, including (S)-citalopram. Photoactivation studies demonstrated irreversible adduction to hSERT by all ligands, but the reduced (S)-citalopram inhibition of labeling by [(125)I]15 compared to that by [(125)I]22 and [(125)I]26 suggests differences in binding mode(s). These radioligands will be useful for characterizing the drug–protein binding interactions for (S)-citalopram at hSERT.